Sustainable freedom of choice: a new concept - Hans-Peter Weikard (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 1996)
The value concept of traditional resource economics is welfare. Therefore, sustainability of welfare is often taken to characterise our obligations to future generations. This paper argues that this view is inappropriate because it leaves no room for future generations autonomy. Future generations should be free to make their own decisions. Consequently freedom of choice is the appropriate value concept on which resource economics should be based. The concept of sustainability receives a new interpretation. Sustainability is a principle of intertemporal distributive justice which requires equitable opportunities across generations.
urn:nbn:de:kobv:517-opus-8484
Keywords: Q20; D63; 330